Testing the Relationship Between Referral Marketing, Consumer Perception and Brand Loyalty In Ayurvedic Products Amongst Women - Sakshee Singh; Garima Malik (ACHSM, 2022)
Ayurveda is an ancient medical method that uses a variety of floras and herbs in preventing sickness and maintaining healthy lifestyle in the Indian Sub-continent. Women consumers in India prefer to use ayurvedic products to protect themselves against medical disorders, personal care and beauty products [1]. During the last decade, the demand for ayurvedic products have grown significantly and therefore every business organization in this sector is aspiring to increase market share by understanding the need of the consumer as well as changing consumer perception through referral marketing and brand preferences. The purpose of this study is to identify links among referral marketing, customer perception, and brand loyalty in relation to ayurvedic products. A structured questionnaire was created for the purpose of survey, and a pilot study was conducted to ensure its validity. Working women and housewives, were the respondents from whom the data were collected. A total of 242 valid responses were collected from the respondents. To examine the link between the latent constructs, structural equation modelling was devised for the constructs- referral marketing, consumer perception and brand loyalty. The study found that referral marketing had positive effect on the perception of the consumer at β = 0.36, CR= 2.59, p=0.000, referral marketing on brand loyalty at β = 0.41, CR= 2.09, p<0.05, accepting the hypothesis H1(Referral marketing has a positive effect on consumer perception); and H2 ( Referral marketing has a positive effect on brand loyalty); Consumer perception affects brand loyalty at β = 0.18, CR= 1.95, p = 0.000, accepting this hypothesis H3. *(The paper presented at the 7th International Conference on Embracing Change & Transformation Innovation and Creativity 26-28 May 2022)